Treatment of Benign Obturator Jaundice and Cholangitis in Elderly and Elderly Patients (Eurasian Medical Research Periodical, 2023)
Non-tumour obturation jaundice and cholangitis are frequent complications of cholelithiasis and are especially severe in elderly and old patients. For the last decades, along with wide prevalence of cholelithiasis, increase of frequency of its complicated forms, including choledocholithiasis, is noted.